Implementation of the Tahsin Program for Students of the Islamic Education Study Program at Ahmad Dahlan University Yogyakarta - Hanif Cahyo Adi Kistoro; Muhammad Kurdiansyah (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2022)
The ability of students to read the Qur'an is very diverse. Some students have been able to read well; others have not. This study aims to describe the implementation of learning al-Qur'ān in the tahsin program for students of Islamic education at Ahmad Dahlan University, Yogyakarta. This research uses qualitative research with a descriptive analysis approach. The research subjects were students and ustadz teaching the Tahsin program, which opened 20 people. The data collection techniques were carried out through observation, interviews and documentation. Data analysis used data reduction procedures, data presentation and data interpretation. The results of this study indicate three essential findings in the form of the program implementation process, the method of implementing the Tahsin program, and the obstacles faced in the implementation of the Tahsin program. The performance of the Tahsin program begins with the selection of ustadz who have the competence to teach Tahsin, followed by program implementation, guidance and examinations. The Tahsin method most widely used by Ustadz teaching is Semaan, Sorogan, classical and Private. Obstacles in the performance of the Tahsin program are classified on internal factors in the form of students' essential ability to recite the Koran, motivation and seriousness of reading the Koran. The hectic external schedule of lectures, the presence of students and the condition of the pandemic cannot all be done directly by learning